Robotic lower-lip mucosal graft ureteroplasty for ureteral stenosis longer than 2 cm: initial experience of thirteen patients - Zhang, Zhaolin; Zeng, Xin; Wu, Yuting; Wu, Gengqing; He, Zhihua; Zhang, Guoxi; Zou, Xiaofeng; Yuan, Yuanhu; Xu, Hui (Frontiers in Surgery, 2024)
ObjectivesTo present our initial experience of robotic ureteroplasty with lower-lip mucosal graft (LLMG) for treating ureteral stenosis longer than 2 cm and evaluate its feasibility and efficacy.Materials and methodsA total of thirteen patients with ureteral stenosis who underwent robotic ureteroplasty with LLMG were retrospectively analyzed. After identification and dissection of the ureteral stenosis segment, the segment was incised longitudinally. Then, the LLMG was harvested according to the characteristics of stenosis and sutured with the ureter in onlay fashion. All procedures were completed successfully.ResultThe median stenosis length was 3.5 cm (ranged: 3.0–4.5 cm). The mean length and width of the LLMG were 3.81 ± 0.60 cm and 1.27 ± 0.26 cm, respectively. The mean operative time and anastomosis time were 212.31 ± 23.06 min and 36.54 ± 6.58 min, respectively. The double-J stent was removed at 8 weeks postoperatively in all patients. Three patients (23.1%) suffered postoperative complications during the follow-up period (range, 6–18 months), including fever, urinary tract infection and stenosis recurrence. The success rate was 92.3% (12/13).ConclusionRobotic ureteroplasty with LLMG is a safe and feasible technique for treating ureteral stenosis.